ANALISIS TINGKAT FINANCIAL LITERACY DAN FINANCIAL BEHAVIOUR KARYAWAN RSUD PARE - Kartini Kartini; Shindy Dwita Nuansari (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2018)
The research was purposed to test the level of financial literacy as well as the factors that can cause different levels of financial literacy of each employee and how financial literacy affects financial behaviour of employees of RSUD Pare. This study took 96 respondents to be the sample with random sampling technique. Methods of data collection is done by distributing questionnaires to employees of RSUD Pare.This research used descriptive statistic, independent t-test, anova, and chi square. Based on descriptive statistic, the level of financial literacy shows that 52 of 96 respondents is in the middle level category. The results of the test show that there are financial literacy differences based on gender, age, education level, and work experience. This study also found that the level of financial literacy owned by employees will give positive impact to their financial behaviour.